Distance Online Exams in Rural India Amid COVID-19: The Engineering Student’s Perspectives - Tandel, Yogendra; Tandel, Roshni; Patel, Jignesh (Journal of Engineering Education Transformations, 2025)
The 2019 coronavirus disease pandemic has shown no concern for artificial borders, and it only took three months to a standstill in the world. During the lockdown period of the COVID-19 around the globe, the entire educational system level has suddenly collapsed. The students’ attitudes of distance online exams during the COVID-19 pandemic among engineering students in rural areas of India were analysed in this study. A survey of 11 questions was prepared and distributed among 858 engineering students of the Gujarat Technological University (GTU), India. The questions include students’ demographics, exams preferences, academic dishonesty, stress experience, factors affecting students’ preference for distance online exams, factors related to students’ exam dishonesty and measures that can be considered to reduce this behaviour and factors contributing to stress as well as behavioural changes related to distance online exams. The descriptive, cross tabulation, and Chi-square tests were used to interpret the data. The results of survey highlighted that approximately 41% students preferred distance online exams. This was significantly associated with student gender, academic degree, effort and time for distance online exams preparation and academic achievements. The main measures considered by students to reduce exam dishonesty included proctoring solutions during online exam. Only 26% students agree with merit-based promotion. About 15% students reported more stress with distance online exams. The internet connectivity and online exam platform appeared as the main factor related to stress in 64%, and 83%, respectively. Online exams had not negative impact on students’ health.